Memória e recordação: valores intangíveis na intervenção contemporânea em património construído nos casos dos conventos de Alferrara - Aleixo, Sofia (Lusitania sacra, 2021)
Intervening in religious heritage is to listen, feel, wander, and interpret the signs that emanate from the space, from the place, whose meanings have changed with the passage of time. In our methodological intervention process, the perception of experiences throughout history is understood as an intrinsic part of the heritage, so we seek to incorporate the memories of use within the scope of the atmospheres that the project may suggest, integrating the senses for the definition of new experiences.